Rheological Property and Thermal Conductivity of Multi-walled Carbon Nano-tubes-dispersed Non-Newtonian Nano-fluids Based on an Aqueous Solution of Carboxymethyl Cellulose. Issue 3 (3rd May 2016) - Tian, J.; He, Z.; Xu, T.; Fang, X.; Zhang, Z.
Abstract : The non-Newtonian nano-fluids with 0.1, 0.5, 1, and 2 wt% of multi-walled carbon nano-tubes have been prepared by dispersing different amounts of multi-walled carbon nano-tubes into an aqueous solution of carboxymethyl cellulose at a weight fraction of 3 wt%, respectively. The nano-fluids exhibit the shear-thinning rheological behavior. The viscosity of the nano-fluid increases with the weight fraction of multi-walled carbon nano-tubes and decreases with the increase in temperature. The thermal conductivity of all the nano-fluids is higher than that of the base liquid. The thermal conductivity enhancement is as high as 14.6% for the nano-fluid containing 2 wt% of multi-walled carbon nano-tubes.